1974
DOI: 10.1093/jaoac/57.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Liquid Chromatographic Determination of Monosaccharides and Glycerol in Aged Distilled Spirits

Abstract: Gas-liquid chromatography was utilized for the analysis of monosaccharides and glycerol in distilled spirits aged in new, charred white oak cooperage. Arabinose, xylose, fructose, glucose, galactose, and rhamnose were identified. Traces of fucose and mannose were indicated. Total concentration of sugars increased from 16 to 37 g/100 L at 100° proof and glycerol from 0.83 to 2.42 g/100 L at 100° proof during aging from 1 through 12 years. Compounds were identified by a comparison of GLC chromatograms of trimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In Fig. 5 we show that overall, hemicellulose was degraded during the maturation process, and a more complex pattern of deterioration emerged from whiskey maturation, rather than a simple loss over time that was expected from previous work on carbohydrate accumulation in bourbon whiskey 17 , 24 . Hemicellulose decreased during aging, to an extent that was significant in the ten-year-old barrel C layer when compared to the new C layer.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In Fig. 5 we show that overall, hemicellulose was degraded during the maturation process, and a more complex pattern of deterioration emerged from whiskey maturation, rather than a simple loss over time that was expected from previous work on carbohydrate accumulation in bourbon whiskey 17 , 24 . Hemicellulose decreased during aging, to an extent that was significant in the ten-year-old barrel C layer when compared to the new C layer.…”
Section: Discussionmentioning
confidence: 56%
“…4B(ii) ) , we found that the quantity of glucose building blocks that could be released from an oak cask into the whiskey held within is equivalent to 300 g from the C layer alone. This amount would result in 1.3 g/L of glucose for a standard sized barrel - a greater amount than estimated in previous indirect studies 17 , 24 . This difference may be explained by the acidification of whiskey that occurs during maturation 17 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation